Effects of Zinc-Layered Filler Incorporation Routes on the Antimicrobial, Mechanical, and Physical Properties of Calcium Caseinate Biopolymeric Films - Maria E. Becerra; Reynell Pérez-Blanco; Oscar Giraldo; Lucia Medina-Pimentel; Christhy V. Ruiz (Molecules)
As the demand for sustainable materials continues to grow, calcium caseinate (Cas) biopolymer films have emerged as promising alternatives to fossil-based plastics. However, their mechanical fragility and high-water sensitivity limit their application in packaging. In this study, we reinforced Cas films with zinc hydroxide nitrate (ZHN) using two incorporation methods: wet (ZHN-w) and dry (ZHN-d). We evaluated how each method affected the dispersion of the filler and, consequently, the functional properties of the films. To our knowledge, this is the first report of ZHN being used in biopolymeric films. Structural and morphological analyses showed better dispersion of ZHN in the wet-incorporated films. These samples exhibited a substantial increase in tensile strength, from 0.75 ± 0.00 MPa to 9.62 ± 2.45 MPa, along with a marked improvement in Young’s modulus. The films also became less soluble in water, more resistant to swelling, and structurally more cohesive. In antimicrobial tests, the ZHN-w films showed stronger inhibition against E. coli and S. aureus. Overall, this approach offers a simple and effective way to enhance protein-based films using food-safe materials, making them suitable for active and bio-based packaging applications.